Developing Artistic Creativity In Early Childhood Through Ecoprint Activities With Punch/Tap Techniques - Suci Ramadhani; Ziana Abbas; Salpina Salpina; Nurhikmah Pohan; Aminah Aminah (Universitas Muhammadiyah Enrekang, 2024)
This research aims to explore the ecoprint technique using the hitting/knocking method to facilitate the development of children's artistic creativity. This qualitative in-depth investigation was carried out at Al Muna Kindergarten, Bireun, involving 15 children aged 4-6 years over a period of 8 weeks. Information gathering strategies included the involvement of researchers in activities, intensive dialogue with teachers and parents, and thorough examination of documentation of children's creations. The results showed a significant increase in all aspects of creativity, with the highest increase in elaboration (80%) and originality (78.95%). Ecoprint techniques have proven effective in stimulating multi-sensory experiences, encouraging exploration of natural materials, and increasing environmental awareness. These findings indicate that ecoprint not only develops artistic creativity, but also strengthens children's connections with nature, in line with the concept of eco-art education. This study highlights the potential for integrating ecoprint techniques in the PAUD curriculum as an innovative approach to developing creativity while increasing environmental awareness. Theoretical and practical implications are discussed, including the need for a redefinition of creativity in a more inclusive and diverse early childhood education context